Optimalisasi Pengenalan Dasar Coding Berbasis Visual untuk Meningkatkan Literasi Digital Siswa Sekolah Menengah - Pohan, Nurmaliana; Kurnia AR, Harlan; Purnama, Pradani Ayu Widya (Forum Kerjasama Pendidikan Tinggi, 2026)
This activity was motivated by the low level of digital literacy and the limited implementation of programming education in secondary schools, which have resulted in students’ lack of understanding of computational thinking from an early age. In fact, this ability is essential for developing critical and creative thinking skills to face the challenges of the Industrial Revolution 4.0 and Society 5.0. This condition highlights the need for educational interventions that introduce the concept of coding starting from the high school level. The workshop aimed to introduce the fundamentals of programming to students of SMA INS Kayutanam through an interactive visual approach using the Scratch platform. This platform was chosen because it is beginner-friendly, featuring a block-based interface that is easy to understand without requiring complex syntax. Through this activity, students learned programming logic, algorithmic thinking, and problem-solving skills in a fun and practical way. The implementation used a project-based learning approach that combined short lectures, demonstrations, hands-on practice, and group discussions. The activity was carried out over two days in the school’s computer laboratory, involving 20 students and two accompanying teachers. Each session focused on introducing programming logic, creating mini projects using Scratch, and evaluating learning outcomes through pre-tests and post-tests. The results showed a significant improvement in students’ understanding, with the average pre-test score increasing from 43 to 82 in the post-test. A total of 90% of participants expressed satisfaction with the activity, and 85% were interested in continuing to learn programming afterward. The visual-based workshop model proved effective in enhancing students’ motivation, confidence, and understanding of technology. This activity not only developed students’ cognitive abilities but also encouraged them to experiment, collaborate, and create through simple projects such as animations or interactive games. The program has the potential to serve as a sustainable community engagement model that integrates educational, technological, and social aspects in supporting the digital transformation of education in Indonesia.